A Design and Build a Smart Waste Collection Platform Based on Community Empowerment - Rudi Setiawan; Apriansyah Apriansyah (Universitas Malikussaleh, 2026)
The existence of waste is one of the common problems that occur in big cities such as in Indonesia. With the existing waste, most of the waste produced cannot be transported to the landfill, causing environmental and health problems. On the other hand, waste also has economic value. Research on waste problems is mostly carried out in a non-ICT platform approach with recommendations for handling waste at high costs. This research proposes a design in waste management using the help of information technology where people can dispose of waste online and people who work as waste haulers get rewarded. This research produces an ICT Platform that can be a massive solution in handling waste problems involving community participation.